Carbon sequestration and financial profitability of coffee agroforestry in Turrialba, Costa Rica and Masatepe, Nicaragua - Salgado Vásquez, Jehnny L. (2010)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2010